In vivo anti‐inflammatory response and bioactive compounds' profile of polyphenolic extracts from edible Argan oil (Argania spinosa L.), obtained by two extraction methods. Issue 12 (1st October 2019) - Kamal, Rabie; Kharbach, Mourad; Vander Heyden, Yvan; Doukkali, Zohra; Ghchime, Rokia; Bouklouze, Abdelaziz; Cherrah, Yahia; Alaoui, Katim
Abstract: The present work examined and assessed the in vivo anti‐inflammatory effect of polyphenolic extracts from Moroccan edible Argan oils ( Argania spinosa L.), extracted by two extraction processes: Hand pressing and mechanical pressing. Chemical properties, such as acidity, peroxide index, ultraviolet indices, total polyphenols composition, fatty acid composition, tocopherol composition, phenolic profiling, and sterol composition were studied. Then, the anti‐inflammatory potential was determined by applying carrageenan, an induced paw edema test in rats. The results revealed an anti‐inflammatory effect of edible Argan oil and indicated a higher efficiency of hand‐pressed oil compared to mechanical‐pressed oil, supporting its traditional use in human health, related to pain and inflammations. The chemical composition of these oils was evaluated, and total polyphenols, tocopherol composition, and some phenolic compounds were found highly concentrated in the hand‐pressed oil. Practical applications: The present study highlights and compares the in vivo anti‐inflammatory effect of polyphenolic compounds, extracted from Argan oil by two processes (hand and mechanical extraction). The study demonstrated the better quality of hand‐pressed oil over mechanically pressed, supporting the traditional uses of this oil in treating several inflammations and pain‐related situations. Moreover, the edible Argan oil may be introduced as a regular diet and food ingredient. Abstract : In vivo anti‐inflammatory effect of polyphenolics extracted from edible Argan oils by either hand or mechanical pressing. Chemical and bioactive profiling of both hand‐ and mechanically pressed edible Argan oils. Comparative study between the two edible Argan oils.